2020
DOI: 10.1029/2020je006510
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Martian Aeolian Sand Dune Deposits Recorded in the Stratigraphy of Valles Marineris and Implications for Past Climates

Abstract: Aeolian sediment transport, deposition, and erosion have been ongoing throughout Mars's history. This record of widespread aeolian processes is preserved in landforms and geologic units that retain important clues about past environmental conditions including wind patterns. In this study we describe landforms within Melas Chasma, Valles Marineris, that occur in distinct groups with linear to crescentic shapes, arranged with a characteristic wavelength; some possess slope profiles analogous to modern sand dunes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Alternatively, in situ investigations have shown surface crusts composed of dust, including on bedforms, that have been suggested to form from slow chemical weathering and/or salt formation as duricrusts (Ewing et al, 2017;McSween et al, 2004;Moore et al, 1999;Sullivan et al, 2008). This apparent induration of dusty bedform surfaces may play a role in the occurrences of lithified dune fields found with largely intact morphologies (Chojnacki et al, 2020;Edgett and Malin, 2000;Milliken et al, 2014).…”
Section: Wind-transported Sediment Grain Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, in situ investigations have shown surface crusts composed of dust, including on bedforms, that have been suggested to form from slow chemical weathering and/or salt formation as duricrusts (Ewing et al, 2017;McSween et al, 2004;Moore et al, 1999;Sullivan et al, 2008). This apparent induration of dusty bedform surfaces may play a role in the occurrences of lithified dune fields found with largely intact morphologies (Chojnacki et al, 2020;Edgett and Malin, 2000;Milliken et al, 2014).…”
Section: Wind-transported Sediment Grain Propertiesmentioning
confidence: 99%
“…For example, aeolian sedimentary strata reveal the sizes of grains transported under past climates and directional changes in transport. Such strata are found throughout Mars' landscape giving us hard evidence for how the wind has interacted with the surface, especially when having speeds greater or equal to the threshold for grain motion (e.g., Banham et al, 2018;Chojnacki et al, 2020;Day et al, 2019;Grotzinger et al, 2005;Milliken et al, 2014). By understanding how the threshold of wind-driven grain motion has changed over time as the climate shifted, we can begin mapping aeolian processes throughout Mars' history using the process-based evidence solidified in martian sedimentary strata.…”
Section: Bedforms: Types and Morphologiesmentioning
confidence: 99%
“…Alternatively, a saltation impact splash mechanism is argued to be efficient in the low dynamic pressure of Mars and permit a wider range of ripple sizes (Sullivan & Kok, 2017; Sullivan et al., 2020). In light of this complexity, and with detections of movement growing as observational baselines extend, it may be premature to draw any strong conclusions about whether any bedforms are completely inactive at present, other than bedforms that preserve impact craters and thus are likely indurated (e.g., Chojnacki et al., 2020; Edgett & Malin, 2000; Golombek et al., 2010).…”
Section: Aeolian Changesmentioning
confidence: 99%
“…However, Silvestro et al (2020) recently reported movement of some brighter bedforms described as megaripples or small TARs, although with inferred sand fluxes two orders of magnitude lower than that estimated for adjacent migrating dunes. Continued observation of TARs and megaripples in other areas of Mars would be needed to confirm whether these bedforms (or at least specific examples of them) are active in the present Mars climate (Chojnacki et al, 2020;Zimbelman, 2019).…”
Section: Bedform Movementmentioning
confidence: 99%
“…Estimated to be approximately 3.5 Ga old [1], the superstructure is related to tectonic rifting of the crust related in part to the loading induced by the Tharsis Volcanic province [1][2][3][4]. This overall tectonic structure has been modified by outflows [5][6][7][8], fluvial processes [7,[9][10][11] (delta, melas), volcanic processes [12][13][14], aeolian processes [15][16][17] and it also thought to contain evidence of glacial modification [18,19]. Its extreme topographic relief influences the atmospheric circulation and creates weather systems unique to the canyon [20,21].…”
Section: Introductionmentioning
confidence: 99%